Constructing 3D Geological Model for Tertiary Reservoir in Khabaz Oil Field by using Petrel software. - Majeed, Yousif N. Abdul; Ramadhan, Dr. Ahmad A.; Mahmood, Dr. Ahmed J. (Journal of Petroleum Research and Studies, 2020)
3D Geological model for tertiary reservoir in khabaz oil field had been constructed by using petrel software. Seven wells have been selected in this study in order to design Petrophysical properties (porosity, water saturation, and permeability). Structural model can be clarified tertiary reservoir in term of geological structures is a symmetrical small anticline fold with four faults. Tertiary reservoir consist of six units are (Jeribe, UnitA, UnitA', UnitB, UnitBE, and UnitE). According to Petrophysical properties, layering had been constructed for each tertiary units. Petrophysical model has been designed using the sequential Gaussian simulation algorithm as a geostatistical method. The results illustrates that Unit B and Unit BE have the best petrophysical properties and the big amount of oil.